On the signed graphs with two distinct eigenvalues - Ramezani F., (Utilitas Mathematica, 2020)
We consider signed graphs, i.e, graphs with positive or negative signs on their edges. We construct some families of bipartite signed graphs with only two distinct eigenvalues. This leads to constructing infinite families of regular Ramanujan graphs. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.